2015
DOI: 10.3846/16484142.2015.1058292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Performance and Durability of a Diesel Common Rail High Pressure Fuel Pump

Abstract: Abstract. This paper presents a comparative experimental study for determining the effect of ethanol on functionality of a high pressure pump of the common rail fuel injection system. For experimental durability tests were prepared two identical fuel injection systems, which were mounted on a test bed for a fuel injection pump. One of the fuel injection systems was feed with diesel fuel; other fuel injection system was fuelled with ethanol-diesel fuel blend. A blend with 12% v/v ethanol and 88% v/v diesel fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Similar results are obtained by Waterland et al; they concluded that increasing ethanol vapor pressure may induce fuel pump vapor lock, which increases fuel pump wear. Moreover, Mickevičius et al found that using low viscosity ethanol fuel might cause wear on the plunger and nozzle needle surfaces. The wear of the plunger and barrel may affect the pump component’s tightness and lubrication.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results are obtained by Waterland et al; they concluded that increasing ethanol vapor pressure may induce fuel pump vapor lock, which increases fuel pump wear. Moreover, Mickevičius et al found that using low viscosity ethanol fuel might cause wear on the plunger and nozzle needle surfaces. The wear of the plunger and barrel may affect the pump component’s tightness and lubrication.…”
Section: Resultsmentioning
confidence: 99%
“…The main properties of the tested fuels are listed in The common rail injection system has been used for the experimental tests. The principal arrangement of the test stand, equipment and apparatus are shown in in another research paper [10].…”
Section: Materials and Methods Of The Researchmentioning
confidence: 99%
“…A E7.7 blend showed similar effect on durability of the injection pump parts than that the diesel fuel but a reduction (around 20%) of nozzle hole effective sections was produced with the blend. In the rest of literature, wear of the injection system parts with bioethanol-diesel blends is observed [38,39].…”
Section: Introductionmentioning
confidence: 99%